Muza Urania Mitylena. Motyw muzalny w tomie poetyckim Jacka Dobrowolskiego „Niepojęte” - Arndt, Aleksandra (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2025)
The article analyses the realisation of the muse motif, with particular reference to Sappho as the ‘tenth muse’ and Urania, in the latest poetic volume by Jacek Dobrowolski.